Talaromyces amestolkiae cell disruption and colorant extraction using imidazolium-based ionic liquids - de Oliveira, Fernanda [UNESP]; Hirai, Patrícia Rie [UNESP]; Teixeira, Maria Francisca Simas; Pereira, Jorge F.B. [UNESP]; Santos-Ebinuma, Valéria C. [UNESP] (Elsevier, 2021)
Recent environmental and health concerns have been pushing the society for the consumption of natural and sustainable products, as for example, the use of natural colorants as additives to impart color. Talaromyces amestolkiae are natural producers of red colorants at both extracellular and cell-bond state, so are very important for the dye industry. T. amestolkiae cells are constituted by a complex and rigid cell wall structure, which contain a major fraction of the total colorants content. The use of environmentally friendly, biocompatible and high-efficiency cell disruption procedures is thus critical for the recovery of the intracellular colorants. An alternative approach using imidazolium-based ionic liquids (ILs) was applied to recover the intracellular colorants from T. amestolkiae fungi. First, the cell disruption ability of a series 1-alkyl-3-methylimidazolium chloride ILs ([Cnmim]Cl) aqueous solutions was determined, assessing both the effect of increasing cationic alkyl chain length (n = 1, 2, 4, 6, 8 or 10) and IL concentration (30% and 45% w/v). [C4mim]Cl showed the highest extraction ability to recover red, orange and yellow colorants. In the second part, the extraction ability of [C4mim]Cl (at 45% w/v in water) was improved, by combining the IL solution chemical treatment with a mechanical (ultrasound-temperature-assisted) cell disrupting method. At this point, the incubation time (at 60 °C and 150 rpm) after sonication, number sonication pulses (5 min ON) and re-extraction effects were screened as parameters for increasing the cell disruption. The mechanical-assisted method allowed an increase of almost 3-fold in the extractive performance of [C4mim]Cl solution, achieving a maximum recovery of 76.07 UA490nm/mL of red colorants. The results demonstrate the potential of [C4mim]Cl solution as chemical cell-disrupting aid in ultrasound-temperature-based methods to improve the recovery of intracellular colorants from complex filamentous fungi cells.
Keywords: Cell disruption; Colorants; Filamentous fungi; Ionic liquids; Talaromyces amesolkiae; Ultrasound